PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPRITUAL TERHADAP KINERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG SIDENRENG RAPPANG - Handayani, Nur (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
Performance is the value of a set of employee behaviors that contribute, one or other positively or negatively, to the completion of organizational goals. The number of samples in this study was 76 employees at PT. Bank Rakyat Indonesia (Persero) Tbk. Kantor Cabang Sidenreng Rappang. To obtain relevant data and information used in this study, the authors used several data collection techniques, namely observation, questionnaires, interviews, and documentation. Data obtained directly from the source of the research object. Primary data sources and secondary data.